A Bench Evaluation of Eight Home-Care Ventilators. - Martínez Castro, Sara; Javier Belda Nacher, Francisco; Delgado Navarro, Carlos; Puig Bernabeu, Jaume (Respiratory Care, 2021)
BACKGROUND: The growing number of patients on home mechanical ventilation has driven considerable progress in the performance and functionality of ventilators, with features comparable with those used in the ICU. However, a publication gap exists in the evaluation and comparison of their performance and each ventilator choice depends on machine characteristics defined by manufacturers. METHODS: We bench tested 8 home-care ventilators that are currently available: Monnal T50, EOVE EO-150, Puritan Bennet 560, Weinmann, PrismaVent 50, Trilogy Evo, Astral 150, and Vivo 60 by using an active lung model. These devices were tested under 18 experimental conditions that combined 3 variables: respiratory mechanics, ventilatory mode, and inspiratory muscle effort. The volume delivered, trigger response, pressurization capacity, and synchronization were analyzed. RESULTS: Significant differences were observed in the performance among the devices. Decreased inspiratory muscle effort caused changes in the delivered volume, which worsened the response-to-trigger time, pressurization capacity, and synchronization. Increased pressure support favored the development of asynchronies. All the ventilators developed asynchronies under at least 1 set of conditions, but the EOVE and Trilogy Evo ventilators showed the fewest asynchronies during the experimental conditions studied. CONCLUSIONS: Great variability in terms of technical performance was observed among the 8 home-care ventilators analyzed. Asynchronies became a major issue when home mechanical ventilation was used under higher pressure-support values and lower muscle efforts. Our results may prove to be useful in helping choose the best suited machine based on a patient's clinical therapy needs.